2011
DOI: 10.1002/chem.201100980
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Functionalization of Graphene with Porphyrin through Cycloaddition Reactions

Abstract: Two types of graphene-based hybrid materials, graphene-TPP (TPP=tetraphenylporphyrin) and graphene-PdTPP (PdTPP=palladium tetraphenylporphyrin), were prepared directly from pristine graphene through one-pot cycloaddition reactions. The hybrid materials were characterized by thermogravimetric analysis (TGA), by TEM, by UV/Vis, FTIR, Raman, and luminescence spectroscopy, and by fluorescence/phosphorescence lifetime measurements. The presence of the covalent linkages between graphene and porphyrin was confirmed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
109
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 98 publications
7
109
0
1
Order By: Relevance
“…Furthermore, the intensity ratio of D-and G-bands of GO is 1.1; while it changes to 1.2 for GO-MnTPP. This change is consistent with the functionalization of graphene oxide through covalent bonding [46]. Besides, the Raman spectrum of the nanocomposite also includes peaks of MnTPP centered at 374, 578, 851, and 999 cm -1 .…”
Section: Structure and Morphologysupporting
confidence: 82%
“…Furthermore, the intensity ratio of D-and G-bands of GO is 1.1; while it changes to 1.2 for GO-MnTPP. This change is consistent with the functionalization of graphene oxide through covalent bonding [46]. Besides, the Raman spectrum of the nanocomposite also includes peaks of MnTPP centered at 374, 578, 851, and 999 cm -1 .…”
Section: Structure and Morphologysupporting
confidence: 82%
“…In addition, graphene-based hybrid nanomaterials, which combine the unique optical, electrical, magnetic and chemical properties of each component have the potential applications in solar cells, sensors and catalysis. Such a hybrid material combining graphene with porphyrin, namely graphene-TPP (tetraphenylporphyrin), has been recently synthesized by cycloaddition reactions [1]. Further, fluorescence spectroscopic studies [1] on graphene-TPP and free TPP-CHO (5-(4-Formylphenyl)-10,15,20-triphenylporphyrin) in dimethylformamide (DMF) (containing similar concentration of porphyrin) have shown that while TPP-CHO shows strong fluorescence (λ peak : 650 nm and 710 nm), fluorescence of porphyrin is quenched significantly in graphene-TPP.…”
Section: Introductionmentioning
confidence: 99%
“…Such a hybrid material combining graphene with porphyrin, namely graphene-TPP (tetraphenylporphyrin), has been recently synthesized by cycloaddition reactions [1]. Further, fluorescence spectroscopic studies [1] on graphene-TPP and free TPP-CHO (5-(4-Formylphenyl)-10,15,20-triphenylporphyrin) in dimethylformamide (DMF) (containing similar concentration of porphyrin) have shown that while TPP-CHO shows strong fluorescence (λ peak : 650 nm and 710 nm), fluorescence of porphyrin is quenched significantly in graphene-TPP. The reduced fluorescence lifetime (< 500ps) of the graphene-TPP as compared to that of free TPP-CHO (∼ 10ns) further confirms the fast quenching of the porphyrin singlet excited state in the hybrid material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…by pyrene derivatives, [97,98] covalent bonding with dienophiles, [99,100] oxygen plasma treatment, [101] doping with 27 heteroatoms, [102][103][104][105] and creation of graphene-inorganic oxide hybrids. [106][107][108] …”
mentioning
confidence: 99%